Severe tungiasis in Western Tanzania: case series - Mazigo, Humphrey D. (J Public Health Africa, 2011)
Tungiasis is caused by infestation with the sand flea (Tunga penetrans). This ectoparasitosis is endemic in economically depressed communities in South American and African countries. However, data on the epidemiology of tungiasis in Tanzania are very limited and the disease does not receive much attention from health care professionals. During a community cross sectional survey in northwest Tanzania, we identified five individuals extremely infested with high number of parasites. A total of 435 lesions were recorded with patients presenting with >75 lesions and showed signs of intense acute and chronic inflammation. Superinfection of the lesions characterized by pustule formation, suppuration and ulceration were common. Loss of nails and walking difficulty was also observed. In Tanzanian communities living under extreme poverty characterized by poor housing condition and inadequate health services, tungiasis may cause severe morbidities. Further studies on risk factors and disease-related behavior of affected populations are needed to design adequate control measures.